PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DI MODERASI KEPEMIMPINAN KEPALA SEKOLAH DI SMK NEGERI SUB RAYON 02 KOTA SEMARANG (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is to examine and analyze the relationship between competence, motivation and principals leadership on teacher’s performance. The research questions that are delivered are (1) does the competence affect the teacher’s performance, (2) Does motivation effect teacher’s performance, (3) Does principal leadership teacher’s performance, (4) Does principal leadership moderate the effect of competency to the teacher’s performance, (5) Does principals leadership moderate the effect of motivation to the teacher’s performance.The population of this research is SMK teachers of civil schools in Sub Rayon 02 SMK Semarang City, the sun is 294. The sample determination uses purposive sampling, the it can be got 100 respondent of sample. The methodf of data collection is usung quesioner. The data analyze technique is using double regresion.The results of this researth shows that competency does not affect the teacher’s performance, motivation affects positively & significanly the teacher’s performance . The principal leadership does not moderate the corelation of competency andteaher’s motivation to their performance Keywords: Teacher’s competency, motivation, teacher’s performance. And principal’s leadership.